KONSEP AKUNTANSI SYARIAH DENGAN NILAI-NILAI MAHAR (Studi Empiris Pada Kantor Urusan Agama Kecamatan Montong) - Lailatus Shoimah; Afifudin Afifudin; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
This study aims to determine the concept of sharia accounting with the dowry values of the Office of Religious Affairs, Montong District, Tuban Regency, East Java. This research is a qualitative research. Data collection techniques that can be in the form of interviews) and observation and data analysis methods are descriptive model methods. The results of the study state that the concept of Islamic accounting in this study uses the concept of financial statements which include 1) Assets, in this study divided into 3 parts, namely dowry in the form of money (current assets), jewelry (fixed assets) and memorizing verses of the Koran (assets). intangible). 2) Obligations, there are 2 categories, namely dowry payments of less than 1 year (current debt) while dowry debts whose payments are more than 1 year (long-term debt). 3) Capital, the application of dowry values is dowry, the capital in question has a function to gain profits and seek the blessing value of the dowry itself. 4) Income and Expenses in the system of dowry values, it is said to be income due to the increase in assets owned by the wife and said to be a burden due to the husband's dowry. Keywords: dowry, sharia accounting and financial statements